Qualitative insights into promotion of pharmaceutical products in Bangladesh: how ethical are the practices? - Mohiuddin, Mahrukh; Faiz Rashid, Sabina; Islam Shuvro, Mofijul; Nahar, Nahitun; Masud Ahmed, Syed (© 2015 BioMed Central Ltd., 2016)
This article was published in BMC Medical Ethics [© 2015 BioMed Central Ltd.] and the definite version is available at: http://bmcmedethics.biomedcentral.com/articles/10.1186/s12910-015-0075-z